Measurement of longwave radiative properties of energy-saving greenhouse screens - Adeel Rafiq; Wook Ho Na; Adnan Rasheed; Jong Won Lee; Hyeon Tae Kim; Hyun Woo Lee (Journal of Agricultural Engineering, 2021)
Light intensity, temperature, and humidity are key factors affecting photosynthesis, respiration, and transpiration. Among these factors, temperature is a crucial parameter to establish an optimal greenhouse climate. Temperature can be controlled by using an appropriate climate screen, which has a considerable impact on crop quantity and quality. The precise measurements of longwave radiative properties of screens are vital to the selection of the most suitable screen for greenhouses so that the desired temperature and a favorable environment can be provided to plants during nighttime. The energy-saving capability of screens can also be calculated by using these properties as inputs in a physical model. Two approaches have been reported so far in the literature for the measurement of these properties, i.e., spectrophotometry and wideband radiometry. In this study, we proposed some modified radiation balance methods for determining the total hemispherical longwave radiative properties of different screens by using wide-band radiometers. The proposed method is applicable to materials having zero porosity, partial opacity, and asymmetric screens with 100% solidity. These materials were not studied previously under natural conditions. The existing and proposed methods were applied and compared, and it was found that the radiometric values obtained from the developed methodology were similar to those previously reported in the literature, whereas the existing method gave unstable results with zero reflectance.